Narasi Visual Kematian Pada Ilustrasi Buku Cerita Rakyat Anak Indonesia - Indrayati, Refita Ika; Setyawan, Pindi; Saidi, Acep Iwan (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Folklore used as a tool to transfer life lesson from generation to generation. In the midst of modern children'sbooks that carry moral as a main theme, folklore must comes with a new adaptation to compete with other stories. Thisadaptation forced to change how sensitive theme must be delivered, such as death. This study aims to explore howIndonesian folklore books that narrated death in terms of images, texts, and relationships built between the twoelements. Using content analysis, this research takes an example of story containing subtheme as story line from fourprinted books of Indonesian children ’s folktales that published between 2015-2017.